Bocas, Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co., [Trinidad and Tobago], 2011)
This postcard shows the Bocas del Dragon (Dragon's Mouth) at daytime. The Bocas Islands which lie between Trinidad and Venezuela, in the Dragon's Mouth, consists of four islands: Gaspar Grande, Chacachacare, Huevos and Monos.
Colour: Sepia with grey; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bocas del Dragón; Dragon's Mouth; Islands--Trinidad and Tobago